110k views
21 votes
Adding linear expressions
(-4x+6) + (x-5)

Adding linear expressions (-4x+6) + (x-5)-example-1
User Sveinungf
by
4.8k points

1 Answer

7 votes

Answer:

Explanation:

Like terms have same variables. Combine like terms.

2) (-4x + 6) + (x - 5) = -4x + 6 + x - 5

= -4x + x + 6 - 5

= -3x + 1

4) (-2x + 10) + (-8x - 1) = -2x + 10 - 8x - 1

= - 2x - 8x + 10 - 1

= - 10x + 9

6) (8x + 9) + (-6x - 1) = 8x + 9 - 6x - 1

= 8x - 6x + 9 - 1

= 2x + 8

User Trevor Freeman
by
4.9k points